Awareness about Oral & Maxillofacial Surgery among Final Year Medical Students and Medical Practitioners of District Kohat, Khyber Pakhtunkhwa - Safi, Sanna; Aslam, Saddique; Khan, Asad (ADVANCES IN BASIC MEDICAL SCIENCES, 2020)
Objective: To gauge awareness about oral & maxillofacial surgery of final year medical students and medical practitioners of District Kohat, Khyber Pakhtunkhwa. Methodology: This study was conducted at KIMS (KMU-Institute of Medical sciences) and its affiliated District Headquarters (DHQ) Hospital, Kohat. Every participant was given a separate questionnaire to fill. The questionnaire comprised of demographics of participant and questions regarding referrals for nine different clinical conditions. Referral options were ENT surgeon, plastic surgeon, general surgeon, OMF surgeon and dental surgeon. Results: OMF surgeon was preferred specialty for treatment of facial trauma by 88% medical students, 88.68 % house officers, 90 % medical officers and 100% consultants. Largest percentage of medical students 40%, house officers 45.3%, medical officers’ 70% and 42.8% consultants referred to OMFS for jaw pathology. For TMPDS, a big number of all i.e. 57% of medical students, 64% house officers, 77.5% medical officers and 71% consultants referred to OMFS. For surgical removal of lower wisdom teeth, 90 % medical students, 79 % house officers, 80 % medical officers, and 85.7 % consultants opted for dental surgeon instead of OMF surgeon. Similarly, for dental implant, 78 % medical students, 69.8 % house officers, 65 % medical officers and 28.5 % consultants deemed dental surgeon appropriate for dental implant. Trigeminal neuralgia was referred to neurosurgeon by 86 % medical students, 68 % house officers, 80 % medical officers and 71.4 % consultants. For facial asymmetry, plastic surgeon was chosen by 75 % of medical students, 73 % of house officers, 60 % of medical officers and 71 % of consultants. Conclusion: Though awareness about managing facial trauma, jaw swelling, TMPDS was found but there is room for establishing awareness of OMFS for most of the other clinical conditions. Keywords: OMFS, OMF surgeon, awareness, medical practitioners